Malicious URLs Detection Based on a Novel Optimization Algorithm - CHENG, Zou F.; BO, Wang; HUA, Zhang X.; WEI, Liu X.; FANG, Zhang B. (IEICE Transactions on Information and Systems, 2021)
In this paper, the issue of malicious URL detection is investigated. Firstly a P system is proposed. Then the new P system is introduced to design the optimization algorithm of BP neural network to achieve the malicious URL detection with better performance. In the end some examples are included and corresponding experimental results display the advantage and effectiveness of the optimization algorithm proposed.